Analisis Implementasi Sistem Elektronik Kinerja (e-kinerja) Pemerintah Provinsi Bengkulu - Eni Denti Denti; Willy Abdillah; Fitri Santi (The Manager Review, 2021)
This purpose of this study are to determine the implementation of the electronic performance system (e- performance) of the Bengkulu Provincial Government, and also to find out what are the supporting and hindering factors. This research was classified as a descriptive research that aims to describe the events in an objective way. The research instruments were questionnaires and conducting interviews with key informants. Furthermore, data from the e- performance application and data from other competent sources are also used. The results of the study reveals the facts that: (1) the implementation of the e-kinerja of the Bengkulu Provincial Government has not been in line with the objectives of e- kinerja itself and (2) the supporting factors for the implementation of e-kinerja include: socialization has been carried out on e-kinerja, there are the employees who already have the ability to develop applications, the Bengkulu Provincial government's e-kinerja has received a security certificate from the BSrE-BSSN; and the inhibiting factors are the lack of competent employees in the field of information technology, there is also, moreover, no specific regulation including Standard Operating Procedure on e-kinerja, there is no special implementation team and supervisor for the implementation. e-kinerja, and to add on, the evaluation of the implementation of e-kinerja has not been carried out regularly.